PROBLEMS OF HUMAN RIGHTS PROTECTION UNDER THE CONDITIONS OF A GLOBAL ECOLOGICAL DISASTER DUE TO POLLUTION OF ENVIRONMENT - Толкачова, Ірина Анатоліївна; Пущик, Ірина Мирославівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: to investigate problems of human rights protection under the conditions of a global ecological disaster due to pollution of environment and suggest ways of their solution. Research methods: general scientific and special methods were used when writing the article. The dialectical method of cognition made it possible to consider the subject matter of research in unity of its social content and legal form, peculiarities of elements of the exercise of right to a secure environment, reveal interactions between them. The historical and legal method was used to analyze the evolution of protection of ecological human rights. In the process of writing the article, such philosophical methods of research were also used: analysis, synthesis, abstraction, deduction and others. An integrated approach to the use of the aforementioned scientific methods made it possible to comprehensively explore problems of human rights protection under a global ecological disaster due to pollution of environment. Results: creation of a single, sanctioned normative act that would regulate the field of ecological human rights is one of the priorities for the contemporary world. Neglecting ecological problems leads to millions of annual deaths, billions of pollution-related diseases, environmental degradation, including water scarcity, depletion of fisheries, natural disasters due to the depletion of natural resources, etc. A horrible picture of globalization of the world testifies about lack of control and interest on the part of citizens, civil organizations, loss of sense of ecological threat, non-using the opportunities for ecological control that leads to global ecological problems as well as starvation and malnutrition, diseases, epidemics, physical and moral exhaustion of human. In order to survive, conscious citizens must unite in civil organizations and form ecological awareness that is able to predict and model ecological processes and in future it will influence on the adoption of relevant laws, determining the directions of ecological activities. Discussion: state of protection of ecological human rights.